Studi di poesia greca tardoantica Atti della Giornata di Studi Università degli Studi di Firenze, 4 ottobre 2012 - gigli, daria; MAGNELLI, ENRICO (Studi e saggi, 2013)
The volume contains the documents of the study day held in Florence on the 4th October 2012 and presents the contributions of nine young scholars of proven competence, belonging to different Italian universities. The multifaceted Greek poetic production of the post-Hellenistic age is investigated through its literary genres and the specific issues it poses: mythological-narrative and didactic epic, theological oracles, pagan and Christian hymnography, an epigram, survival of the poetic expressive code in the prose of the early Byzantine age. The essays are different in perspective - critical-textual, exegetical, historical-literary - but are united by a solid philological basis; moreover, each of them offers innovative ideas that make the volume of great interest for the international scientific community.